Surgical Complications of Typhoid Fever - Faisal G. Bhopal, Faryal Azhar, Shahid Mahmood, Sadaf Faisal Bhopal , Kamran Faisal Bhopal (Journal of Rawalpindi Medical College, 2013)
Background: To study surgical complications of typhoid fever. Methods: In this descriptive study 97 patients with history of typhoid fever, with surgical complication, were enrolled. Patients were operated through midline incision / Right subcostal. In patients, who were haemodynamically stable and with a short history (< 48 hrs) simple closure of perforation with interrupted vicryl 2/0 stitches was done. In haemodynamically unstable patients presenting late, (> 48 hrs) loop Ileostomy was made in the right iliac fossa. In patients with acaculus (typhoid) cholecystitis, perforation or gangrene of gall bladder, cholecystectomy was performed. In patients with gastrointestinal haemorrhage, involved area was identified and resection and end to end anastomosis was performed Result: Majority (87.6%) of the patients presented with small bowel perforation. Exteriorization of gut with primary closure was performed in 87.62%. Postoperatively wound infection was seen in 24.74%. Fecal fistulae and ileostomy prolapse were seen in 3.09% and 5.15%, respectively. Overall mortality was 10.3%. Conclusion: Typhoid fever still remains a cause of concern for surgeon, because of its prevalence in our region. Persistent or severe enteric fever usually culminates in severe surgical complications.